SOLVABILITY OF COUPLED SYSTEMS OF FRACTIONAL ORDER INTEGRO-DIFFERENTIAL EQUATIONS - Hashem, H.H.G.; El-Sayed, A.M.A. (IndoMS, 2013)
We present existence theorems for coupled systems of quadratic integral equations of fractional order. As applications we deduce existence theorems for twocoupled systems of Cauchy problems. Also, an example illustrating the existence theorem is given.DOI :Â http://dx.doi.org/10.22342/jims.19.2.167.111-121